2017
DOI: 10.1177/0956797617729816
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Causal Estimates for Links Between Spanking and Children’s Externalizing Behavior Problems

Abstract: Establishing causal links when experiments are not feasible is an important challenge for psychology researchers. The question of whether parents’ spanking causes children’s externalizing behavior problems poses such a challenge because randomized experiments of spanking are unethical and correlational studies cannot rule out potential selection factors. This study used propensity score matching based on the lifetime prevalence and recent incidence of spanking in a large and nationally representative sample (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…Scholars, practitioners, and policy makers continue to debate about the merits of spanking, in part due to correlational evidence. Nevertheless, the highest quality studies, which employ various methods to statistically control for possible confounders (e.g., Gershoff, Sattler, & Ansari, 2018 ; Ma, Grogan-Kaylor, & Lee, 2018 ), consistently demonstrate negative effects of spanking, and even “small effects can translate into large societal impacts” ( Gershoff & Grogan-Kaylor, 2016 , p. 465). At best, spanking is likely an ineffective practice for helping children develop socially and emotionally; at worst, it is likely harmful to children across the world.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars, practitioners, and policy makers continue to debate about the merits of spanking, in part due to correlational evidence. Nevertheless, the highest quality studies, which employ various methods to statistically control for possible confounders (e.g., Gershoff, Sattler, & Ansari, 2018 ; Ma, Grogan-Kaylor, & Lee, 2018 ), consistently demonstrate negative effects of spanking, and even “small effects can translate into large societal impacts” ( Gershoff & Grogan-Kaylor, 2016 , p. 465). At best, spanking is likely an ineffective practice for helping children develop socially and emotionally; at worst, it is likely harmful to children across the world.…”
Section: Discussionmentioning
confidence: 99%
“… 6 For example, studies have found that spanking was associated with increased aggression, 7 behavioral problems, 8 antisocial behavior, 9 , 10 and externalizing behaviors during childhood. 1 , 11 , 12 Many of the previous studies have focused on the early developmental period of preschool or young, school-aged children, with the time between assessments varying across studies. Less is known about how physical punishment in childhood is associated with antisocial behaviors in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 50 years, the physical punishment of children has attracted considerable empirical attention from social scientists. This research suggests, overwhelmingly, that spanking does more harm than good (see Ferguson, 2013;Gershoff & Grogan-Kaylor, 2016;Gershoff, Sattler, & Ansari, 2017;Gromoske & Maguire-Jack, 2012). Physical punishment has also been acknowledged internationally as a violation of human rights (United Nations, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, as defenders of the research remind us, much of the correlational evidence comes from studies that are statistically rigorous and use multi-variate models that attempt to control for extraneous variables. These studies have consistently documented that physical punishment increases the risk that children will experience harm or develop behavior problems, suggesting a causal pathway from parental physical punishment to negative developmental outcomes (Gershoff & Grogan-Kaylor, 2016;Gershoff, Sattler, & Ansari, 2017). Plus, defenders of the research argue it is neither feasible nor ethical, to randomly assign parents and children into experimental and control groups.…”
Section: Physical Punishment Is Ineffective and Harmfulmentioning
confidence: 99%